2015
DOI: 10.1002/bmb.20845
|View full text |Cite
|
Sign up to set email alerts
|

Myoglobin structure and function: A multiweek biochemistry laboratory project

Abstract: We have developed a multiweek laboratory project in which students isolate myoglobin and characterize its structure, function, and redox state. The important laboratory techniques covered in this project include sizeexclusion chromatography, electrophoresis, spectrophotometric titration, and FTIR spectroscopy. Regarding protein structure, students work with computer modeling and visualization of myoglobin and its homologues, after which they spectroscopically characterize its thermal denaturation. Students als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…The third is promoting students' independent learning. There does not seem to be any need to develop tasks using a molecular viewer for the student to acquire knowledge of proteins, since there are other techniques of learning using molecular models 3–10 . However, the student's involvement in the tasks, which incorporate procedural knowledge P2 regarding the use of software features for high‐school students, may promote independent learning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The third is promoting students' independent learning. There does not seem to be any need to develop tasks using a molecular viewer for the student to acquire knowledge of proteins, since there are other techniques of learning using molecular models 3–10 . However, the student's involvement in the tasks, which incorporate procedural knowledge P2 regarding the use of software features for high‐school students, may promote independent learning.…”
Section: Discussionmentioning
confidence: 99%
“…Visual literacy in biochemistry can greatly assist experts and students, both of whom use such molecular models to study protein structure and function 1,2 . Most of the curricula for students in tertiary education suggest three main means of displaying visual information using molecular models of proteins: (i) retrieving structure files from the Research Collaboratory for Structural Bioinformatics Protein Data Bank (RSCB‐PDB) and visualizing them using PyMol 3–6 or another molecular viewer 7–10 ; (ii) encouraging the haptic perception of protein structures using tactile molecular models in combination with visualization of molecular models 11–16 ; (iii) using virtual reality or augmented reality in 3D 17–19 . The wide scale use of molecular models as a visualization tool for learning about proteins has prompted the development of frameworks for evaluating visual literacy in biochemistry 1,2,20 for teachers and students in tertiary education 21–26 …”
Section: Introductionmentioning
confidence: 99%
“…Less appreciated, however, is its role in mitochondrial functioning, including the synthesis of cofactors and enzymes necessary for cellular respiration. 26,27 Consequently, highly metabolic cells such as cardiomyocytes and skeletal muscle cells are dependent on iron for optimum functioning. 10 A randomised controlled trial (RCT) by Melenovsky et al showed that ID reduces aerobic respiration and citric acid cycle enzyme activity in advanced HF.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…PDB‐101 content is primarily developed by RCSB PDB team members. A quarterly Education Corner publishes descriptions of how other researchers and educators (e.g., 51–59 ) are using PDB data in classrooms, art, and science outreach.…”
Section: Community Interactions and Impactmentioning
confidence: 99%